(untitled) (Spectrum Journal of Innovation, Reforms and Development, 2026)
The rapid development of modern industry and the construction sector has intensified the need for rational utilization of natural resources. Due to the limited availability of natural raw materials, there is an increasing demand for their conservation, recycling, and the development of alternative materials. As a result, the concept of artificial raw materials has emerged and is now widely applied across various industries. This article presents an overview of artificial raw materials and analyzes their principal physical and chemical properties.